Dectin-1-Targeted Antifungal Liposomes Exhibit Enhanced Efficacy - Suresh Ambati (American Society for Microbiology, 2019)
ABSTRACT Aspergillus species cause pulmonary invasive aspergillosis resulting in nearly 100,000 deaths each year. Patients at the greatest risk of developing life-threatening aspergillosis have weakened immune systems and/or various lung disorders. Patients are treated with antifungals such as amphotericin B (AmB), caspofungin acetate, or triazoles (itraconazole, voriconazole, etc.), but these antifungal agents have serious limitations due to lack of sufficient fungicidal effect and human toxicity. Liposomes with AmB intercalated into the lipid membrane (AmB-LLs; available commercially as AmBisome) have severalfold-reduced toxicity compared to that of detergent-solubilized drug. However, even with the current antifungal therapies, 1-year survival among patients is only 25 to 60%. Hence, there is a critical need for improved antifungal therapeutics. Dectin-1 is a mammalian innate immune receptor in the membrane of some leukocytes that binds as a dimer to beta-glucans found in fungal cell walls, signaling fungal infection. Using a novel protocol, we coated AmB-LLs with Dectin-1’s beta-glucan binding domain to make DEC-AmB-LLs. DEC-AmB-LLs bound rapidly, efficiently, and with great strength to Aspergillus fumigatus and to Candida albicans and Cryptococcus neoformans, highly divergent fungal pathogens of global importance. In contrast, untargeted AmB-LLs and bovine serum albumin (BSA)-coated BSA-AmB-LLs showed 200-fold-lower affinity for fungal cells. DEC-AmB-LLs reduced the growth and viability of A. fumigatus an order of magnitude more efficiently than untargeted control liposomes delivering the same concentrations of AmB, in essence decreasing the effective dose of AmB. Future efforts will focus on examining pan-antifungal targeted liposomal drugs in animal models of disease. IMPORTANCE The fungus Aspergillus fumigatus causes pulmonary invasive aspergillosis resulting in nearly 100,000 deaths each year. Patients are often treated with antifungal drugs such as amphotericin B (AmB) loaded into liposomes (AmB-LLs), but all antifungal drugs, including AmB-LLs, have serious limitations due to human toxicity and insufficient fungal cell killing. Even with the best current therapies, 1-year survival among patients with invasive aspergillosis is only 25 to 60%. Hence, there is a critical need for improved antifungal therapeutics. Dectin-1 is a mammalian protein that binds to beta-glucan polysaccharides found in nearly all fungal cell walls. We coated AmB-LLs with Dectin-1 to make DEC-AmB-LLs. DEC-AmB-LLs bound strongly to fungal cells, while AmB-LLs had little affinity. DEC-AmB-LLs killed or inhibited A. fumigatus 10 times more efficiently than untargeted liposomes, decreasing the effective dose of AmB. Dectin-1-coated drug-loaded liposomes targeting fungal pathogens have the potential to greatly enhance antifungal therapeutics.